Rights analysis power relations among EAP stakeholders - Mohd Basari, Shahrul Nizam (2018)
Needs analysis and related concepts (learner needs, needs assessment) have been discussed and presented in the context of ESP/EAP in a number of prominent works throughout the decades. Notwithstanding, Benesch (2001a) sees needs analysis in ESP as merely descriptive; it does not address questions about unequal power in academia, sociopolitical issues and their effects on curriculum, and social issues affecting students’ current academic lives. Hence, she argues for a critical approach to target situations in needs analysis, and uses the term ‘rights analysis’ to express how power relations are practiced in educational decision-making. In a rights analysis carried out on the findings of a needs analysis in an EAP course at a public university in Malaysia, the interview data revealed the emergence of power struggles and power relationships among the stakeholders of the course. This paper discusses these two themes in the context of challenges faced by EAP stakeholders. The themes are one part of the findings of a larger study to investigate academic writing needs in an EAP course. They emerged during the analysis of interviews with EAP lecturers, engineering and human sciences lecturers, and engineering and human sciences students who were taking the EAP course.